How do smart city pilots affect the ESG performance of manufacturing firms? evidence from China - Tang, Haisheng; Wang, Jeng-Bang; Ou, Chung-Ya (Frontiers in Environmental Science, 2024)
Introduction: The existing literature extensively covers factors influencing environmental, social, and governance (ESG) performance. However, there’s a lack of studies exploring the relationship between smart cities and ESG performance. This gap is surprising, particularly considering the significant role that governments in developing countries play in leading smart city initiatives. Methods: As the impact of smart city pilot (SCP) policies, initiated by governments, on the ESG performance of manufacturing firms lacks verification, our study leverages SCP as a quasi-experiment to examine the effects of smart city development on this performance. Data was collected from 2,229 listed manufacturing firms in China from 2009 to 2020. Results: Our findings indicate a substantial increase in ESG performance among manufacturing firms due to SCP implementation. Heterogeneity analysis reveals that the positive influence of SCP is primarily advantageous for non-state-owned enterprises. Geographically, SCP significantly enhances corporate ESG performance in eastern and central China, with more muted effects observed in the western region. Two key mechanisms driving the enhancement of corporate ESG performance due to SCP are the promotion of green innovation investment and the improvement of internal control quality. Discussion: This paper provides valuable insights for policymakers and business leaders in China and other emerging economies. It guides them in fortifying ESG performance, thereby facilitating sustainable corporate growth.